2001
DOI: 10.1590/s0100-879x2001000100008
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and ultrastructural analysis of different pituitary cell populations in undernourished monkeys

Abstract: Undernutrition elicited by a low-protein diet determines a marked reduction of hypophyseal activity and affects the function of the respective target organs. The objective of the present investigation was to study the ultrastructural and quantitative immunohistochemical changes of the different pituitary cell populations in undernourished monkeys that had been previously shown to have significant changes in craniofacial growth. Twenty Saimiri sciureus boliviensis monkeys of both sexes were used. The animals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Some reported studies have shown that food deprivation decreased growth-hormone (GH)-releasing hormone and consequently the GH serum levels, which could easily explain the low weight gain of these animals [1]. We have also shown that pups whose mothers were subjected to protein or energy malnutrition during lactation present an alteration in the leptin serum concentration [2], which could also be related to the low weight gain of the animals.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Some reported studies have shown that food deprivation decreased growth-hormone (GH)-releasing hormone and consequently the GH serum levels, which could easily explain the low weight gain of these animals [1]. We have also shown that pups whose mothers were subjected to protein or energy malnutrition during lactation present an alteration in the leptin serum concentration [2], which could also be related to the low weight gain of the animals.…”
Section: Discussionmentioning
confidence: 81%
“…It could possibly be a multifactorial disease, affecting several organs and functions, which may not be related to each other. Previous works have shown that malnutrition can affect several systems [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deficiency in body weight gain seen in malnourished offspring could result from a reduction or absence of growth hormone (GH) because food deprivation reduces the number of GH secretory cells, as shown by immunostaining of hypothalamic sections for GH-releasing hormone (GHRH) and quantification of the mRNA levels for GHRH and GH (Brogan et al, 1997;Cónsole et al).…”
Section: Discussionmentioning
confidence: 99%
“…Undernutrition has a wide variety of effects on the endocrine system (Moura et al, 1996;Cónsole et al, 2001;Teixeira et al, 2002;) that can reduce the body weight (Passos et al, 2000;Teixeira et al, 2002;Santos et al, 2004;Fernandes et al, 2007;Fernandes et al, 2008). Indeed, the use of body weight as a measure of growth has shown that protein malnutrition produces smaller-sized individuals (Pucciarelli, 1981;Cotheran et al, 1985;Cameron & Experimental procedures and diets.…”
Section: Introductionmentioning
confidence: 99%